Protective Effect of Hydroxytyrosol Against Oxidative Stress Induced by the Ochratoxin in Kidney Cells: in vitro and in vivo Study - Crupi, Rosalia; Palma, Ernesto; Siracusa, Rosalba; Fusco, Roberta; Gugliandolo, Enrico; Cordaro, Marika; Impellizzeri, Daniela; De Caro, Carmen; Calzetta, Luigino; Cuzzocrea, Salvatore; Di Paola, Rosanna (Frontiers in Veterinary Science, 2020)
Ochratoxin-A (OTA) is a mycotoxin that is a common contaminant of food products for both humans and animals. This mycotoxin has several toxic effects. In particular, ochratoxin has significant nephrotoxic potential. In fact, OTA has been described as being responsible for naturally occurring animal and human kidney disorders. The toxicity of this mycotoxin involves the induction of the oxidative stress pathways. Therefore, in the present study, we wanted to evaluate the potential protective effects of hydroxytyrosol (HT), a phenolic constituent with potent antioxidant activity, of extra virgin olive oil in three different renal cell lines, the Madin-Darby canine kidney cell line (MDCK), a pig kidney cell line (LLC-PK1), and a rabbit kidney cell line (RK 13), and in rats. Our results clearly showed that renal cells respond to OTA exposure by reducing cell proliferation and the induction of oxidative stress. Pre-incubation of the cells with HT prevented the cellular cytotoxicity and increased reactive oxygen species (ROS) levels induced by OTA. In addition, the antioxidative activity of HT was studied by measuring malondialdehyde (MDA) and lactate dehydrogenase (LDH) levels and nitrosative stress. Finally, we investigated the capability of HT (20 mg/kg, intraperitoneally) to act in vivo. In rats, HT reduced oxidative stress and collagen accumulation in the kidney and counteracted the augmentations in AST, ALT, and creatinine levels following OTA induction (250 μg/kg for 90 days orally). In conclusion, our findings demonstrate that HT is able to protect three renal cell lines from the damage induced by OTA and protect the kidneys of rats. Therefore, the use of this compound could be an important strategy for the treatment and prevention of this type of kidney dysfunction.